2023
DOI: 10.3389/fcimb.2022.1105811
|View full text |Cite
|
Sign up to set email alerts
|

Gastric microbiota in gastric cancer: Different roles of Helicobacter pylori and other microbes

Abstract: Gastric cancer (GC) is one of the leading causes of cancer-related deaths worldwide. The gastric microbiota plays a critical role in the development of GC. First, Helicobacter pylori (H. pylori) infection is considered a major risk factor for GC. However, recent studies based on microbiota sequencing technology have found that non-H. pylori microbes also exert effects on gastric carcinogenesis. Following the infection of H. pylori, gastric microbiota dysbiosis could be observed; the stomach is dominated by H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…It will be a further point of interest to understand the role of bacteria carried in the saliva and transiting the stomach and whether, in the absence of H. pylori, some of them become candidates for resilience and explain the entity of H. pylori-negative gastritis. The contributing role of bacteria in the development of severe gastritis into gastric cancer is shown in animal experiments and humans, and more insights are expected in this area 161,368,369 . Vaccine development should be pursued and lessons from previous failures will help in new approaches 172 .…”
Section: Discussionmentioning
confidence: 99%
“…It will be a further point of interest to understand the role of bacteria carried in the saliva and transiting the stomach and whether, in the absence of H. pylori, some of them become candidates for resilience and explain the entity of H. pylori-negative gastritis. The contributing role of bacteria in the development of severe gastritis into gastric cancer is shown in animal experiments and humans, and more insights are expected in this area 161,368,369 . Vaccine development should be pursued and lessons from previous failures will help in new approaches 172 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, increasing evidence has demonstrated that gut microbiota plays an essential role in health and disease ( Stewart et al, 2020 ; Guo et al, 2023 ). Studies have shown that the gut microbiota is associated with radiotherapy for colorectal cancer 11-13 .…”
Section: Discussionmentioning
confidence: 99%
“…As H. pylori is a bacterium that affects and is affected by the gastric microbiota, it is closely related to other bacteria in the progression of GC. Non- H. pylori microorganisms interact with H. pylori in gastric carcinogenesis ( Guo et al, 2023 ). Successful H. pylori eradication can reverse gastric microbiota dysbiosis ( Guo et al, 2020 ; Guo Q. et al, 2022 ), and its high eradication rate is related to specific flora members ( Niu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%